RESEARCH OF FACTORS WHICH INFLUENCE THE QUALITY OF OPTIC TELESCOPIC DEVICES: RESEARCH OF FACTORS WHICH INFLUENCE THE QUALITY OF OPTIC TELESCOPIC DEVICES - Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Defining of the information quantity as a function from the adaptation brightness. It has been found that there exists a correlation between the information quantity which is transferred by a telescopic appliance and the eye and the background brightness in which the object will be observed and this allows to define an informational criterion about the quality of the apparatus as a function from the background brightness. The given formulas are used to evaluate concrete apparatuses for observation, which are applied in distant objects discovery from the board of man-navigated spacecrafts and they are in fact used there.